Interferência de Poa annua L. em Lolium multiflorum Lam. em função do ambiente de competição e do momento de estabelecimento - Conceição, Danúbia Quadros da (2021)
The species Poa annua, of the poaceae family, has been shown to occur in pasture environments in the state of Rio Grande do Sul. There is a great presence of this species as a weed during the winter period, occupying an extensive area of pastures, competing with ryegrass forage, for example. The objective was to evaluate the interference of Poa annua in different populations and conditions of competition with a single ryegrass plant. Two experiments were carried out in a completely randomized design with five replications in a 3x5 factorial scheme, testing different competition strata (aerial part, root system, and aerial part and root system) and ryegrass establishment times (together or after the competing species), with growing populations of Poa annua (0, 35, 139, 279, 419 plants m-2). The variables analyzed 50 days after the start of the competition were plant height, length of the root system, stem diameter, and green mass of the aerial part and ryegrass root system. The variables were subjected to analysis of variance, normality (Shapiro-Wilk) and homogeneity (O’Neill-Matthews). The levels of factor A were differentiated by calculating the confidence interval of the averages and in factor B the complementary analysis was by quadratic regression. In the first experiment, interaction between factors was observed for the variables root length, stem diameter and green mass of the aerial part and root system. For the second experiment, there was an interaction between factors for all variables. It is concluded that the negative interference of Poa annua on ryegrass is greater when the plants compete entirely for the resources of the environment, that is, for the aerial part and root system. There is a detrimental effect on ryegrass growth and less competitive ability when it is established after Poa annua.